ChemInform Abstract: Privileged Scaffolds in Synthesis: 2, 5‐Piperazinediones as Templates for the Preparation of Structurally Diverse Heterocycles. Issue 4 (31st January 2013) - Gonzalez, Juan F.; Ortin, Irene; de la Cuesta, Elena; Menendez, J. Carlos
Abstract Review: 60 refs.